2022
DOI: 10.1111/jace.18447
|View full text |Cite
|
Sign up to set email alerts
|

Self‐reduction and enhanced luminescence in transparent Mn2+‐doped mullite glass‐ceramics derived from EMT‐type zeolite

Abstract: Mn2+ activated glass‐ceramic (GC) has received tremendous attention in the exploration of luminescent materials for solid‐state lighting due to the high stability, broad red emission, and low toxicity. However, the doped Mn2+ ions still suffer from the oxidation and uncontrollable ions migration during the melting process of conventional preparation techniques, which is detrimental to the luminescence performance. Herein, transparent Mn2+‐doped mullite GCs have been prepared at low temperature (∼850°C) via the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…The profiles of the spectra are very similar to each other. The main vibration signals are well identified according to the fundamental vibrating units, namely, P 4 O 12 4− ring anion in the phosphate framework reported in Refs. [19][20][21].There are several strong bands at 1300 cm −1 (v as PO 2 ), 1100 and 1010 cm −1 (v s PO 2 ), and 920-1000 cm −1 (v as P-O-P).…”
Section: Phase Formation Identification and Structurementioning
confidence: 62%
See 4 more Smart Citations
“…The profiles of the spectra are very similar to each other. The main vibration signals are well identified according to the fundamental vibrating units, namely, P 4 O 12 4− ring anion in the phosphate framework reported in Refs. [19][20][21].There are several strong bands at 1300 cm −1 (v as PO 2 ), 1100 and 1010 cm −1 (v s PO 2 ), and 920-1000 cm −1 (v as P-O-P).…”
Section: Phase Formation Identification and Structurementioning
confidence: 62%
“…It has been found that most metaphosphate compounds have PO 4 tetrahedral linked together in infinite chains. In MgP 2 O 6 , four PO 4 tetrahedra are connected together in a ring to construct P 4 O 12 4− groups. Only a few metaphosphates with such kind of atom arrangement have been reported.…”
Section: Phase Formation Identification and Structurementioning
confidence: 99%
See 3 more Smart Citations